Mekanisme Pengenaan Sanksi Emiten, Perusahaan Publik, dan Profesi Penunjang Pasar Modal Sebagai Implementasi Good Corporate Govenance (Studi Kasus pada Kantor OJK Pusat) - Dhimas Mohammad Kautsar; Rosdini , Dini (P3M Politeknik Negeri Bengkalis, 2025)
The growth of investors in Indonesia during the 2020–2024 period shows a positive trend, yet it is not matched by adequate investment literacy, creating potential for misuse by financial service providers, issuers, public companies, and capital market supporting professionals through information violations. This study examines the role of the Financial Services Authority in enforcing Good Corporate Governance through administrative sanctions to maintain capital market stability. Using a qualitative method with a desk research approach and secondary data analysis (OJK regulations, company public reports, and written confirmations requested from OJK), as well as case studies of companies across various industries, the research reveals that OJK's progressive sanctions (from warnings to license revocations) are not yet fully effective. Technical constraints in the XBRL system, low literacy among new issuers, and inconsistencies in the sanctions database are among the inhibiting factors. Violations such as insider trading and delayed disclosure of information not only damage issuers' reputations (e.g., billions of rupiah in fines for PT X) but also threaten investor confidence. This study recommends integrating an automated warning system, enhancing OJK-BEI collaboration in risk-based technical training, and strengthening Internal Control Units (SPI) to mitigate asymmetric information. The research emphasizes that holistic enforcement of sanctions not only protects novice investors but also serves as a foundation for the macroeconomic stability of Indonesia's capital market.